21 Role of lipoprotein (A) in the development of young (<45 years) ST-elevation myocardial infarction. (6th October 2022) - McCaughey, C; Kumar, R; Khan, B; Murphy, G; Teehan, S; Daly, C
Abstract : Introduction: Lipoprotein (a) [Lipo (a)] is a low-density lipoprotein (LDL) with an additional apolipoprotein (a) moiety, which has been associated with increased risk of ischaemic heart disease (IHD). The role in the development of acute ST-Elevation Myocardial Infarction in 'young' (≤ 45 years) patients has not previously been studied. This novel observational study aims to determine the association between elevated levels of Lipo (a) and development of STEMI ≤ 45 years, using comparisons with both those presenting with STEMI >45 years and previously healthy controls undergoing computed tomography coronary angiography (CTCA). Methods: All STEMI presentations to a single tertiary centre over a 75-month period were retrospectively reviewed. Patients ≤ 45years at time of presentation were invited to attend for a global cardiovascular risk assessment (medical history, Body Mass Index (BMI) and waist circumference (WC) measurement, repeat blood lipid analysis, lipo (a) level and Familial Hypercholesterolaemia (FH) screening). Consecutive patients >45years presenting with STEMI were prospectively recruited, with clinical measurements obtained at index presentation. Patients with non-obstructed coronary arteries, coronary artery dissection, or coronary vasospasm without thrombosis at angiography were excluded. Patients without a prior diagnosis of ischaemic heart disease (IHD) undergoing computed coronary angiography were prospectively recruited, with clinical characteristics and lipoprotein (a) levels obtained. Degree of stenosis was used to stratify patients with normal coronaries (<20%), non-obstructive coronary artery disease (CAD) (20–70%), or obstructive CAD (>70%). Results: Over a 75-month period 9% of STEMIs (244/2630) were young. The recruitment of patients <45 years with STEMI (n=58) is described in figure 1 . In total, 51 consecutive patients >45 years who presented with STEMI and 91 patients who presented for CTCA were recruited. Baseline characteristics and Lipo (a) results for each cohort are summarised in table 1 . Of patients undergoing CTCA, 47% (43/92) had normal coronaries, 32% (29/92) NOCA and 21% (19/92) had obstructive CAD. STEMI patients <45 years had a significantly higher rate of elevated Lipoprotein (a) (31/58; 53%) compared with >45years (16/50; 32%; p=0.025) and those undergoing CTCA (26/91; 29%; p=0.002). Lipoprotein (a) level was significantly higher in those <45 years (184 (73–236.8); (Q1–3)) compared those >45 years (184 (73–236.8); p=0.025), and those presenting for CTCA (50 (24–198); p=0.007), ( figure 2 ). There were no significant differences in rates of detectable (>20nmol/L) Lipoprotein (a) (p=0.667) or rates of markedly elevated Lipoprotein (a) (>Cohort Q3) between groups (p=0.064). Conclusion: Patients presenting with young (<45 years) STEMI have both higher rates of elevated Lipoprotein (a) and higher absolute levels of Lipoprotein (a), compared with those presenting at an older age and those with no history of IHD. These findings suggest that elevated levels of Lipoprotein (a) have a positive, non-linear association with the development of STEMI at younger ages.